Runx2 activity in committed osteoblasts is not essential for embryonic skeletogenesis. (August 2014) - Adhami, Mitra D.; Rashid, Harunur; Chen, Haiyan; Javed, Amjad
Abstract Runx2 transcription factor is essential for the development of mineralized tissue, and is required for osteoblast commitment and chondrocyte maturation. Mice with global deletion of Runx2 exhibit complete failure of bone tissue formation, while chondrocyte-specific Runx2-deficient mice lack endochondral ossification. However, the function of Runx2 after commitment of mesenchymal cells to the osteoblast lineage remains unknown. Here, we elucidate the osteoblast-specific requirements of Runx2 during development of the tissue. Runx2 was deleted in committed osteoblasts using Cre-recombinase driven by the 2.3kbCol1a1 promoter. Surprisingly, Runx2ΔE8/ΔE8 mice were born alive and were essentially indistinguishable from wild-type littermates. At birth, we failed to detect any alterations in skeletal patterning or extent of bone development in homozygous mutants. However, by 4 weeks of age, mutant mice showed obvious growth deficiencies, and weighed 20–25% less than sex-matched wild-type littermates. Micro-CT analysis of the hindlimb revealed a dramatic decrease of 50% in both cortical and trabecular bone volume compared with wild-type mice. Consistent with this observation, trabecular number and thickness were decreased by 51% and 21%, respectively, and trabecular space was increased by 2-fold in limbs of Runx2ΔE8/ΔE8 mice. In addition to poor acquisition of bone mass, the average density of hydroxyapatite was markedly decreased in bone of Runx2ΔE8/ΔE8 mice. Together, these findings demonstrate that loss of Runx2 activity in committed osteoblasts impairs osteoblast function, and that Runx2 is critical for postnatal, but not embryonic endochondral ossification.